Experimental and numerical simulations of bottom hole temperature and pressure distributions of supercritical CO2 jet for well-drilling - 王瑞和 霍洪俊 黄志远 宋慧芳 倪红坚 (Journal of hydrodynamics. Series B, 2014)
The supercritical carbon dioxide （SC-CO2） drilling is a novel drilling technique developed in recent years. A detailed study of temperature and pressure distributions of the SC-CO2 jet on the bottom of a well is essensial to the SC-CO2 drilling. In this paper, the distributions of pressure and temperature on the bottom of the hole during the SC-CO2 jet drilling are simulated experimentally and numerically, and the impacts of the nozzle diameter, the jet length, and the inlet pressure of the SC-CO2 jet are analyzed. It is shown that, the bottom hole temperature and pressure increase with the increase of the nozzle diameter, and the bottom hole temperature reduces and the pressure increases first and then decreases with the increase of the jet length, indicating that the jet length has an optimum value. The increase of the inlet pressure can increase the temperature and pressure on the bottom, which has a positive effect on the drilling rate.